AGILITY STRATEGY: INVESTMENT DIVERSIFICATION APPROACH TO SHARIA FINANCIAL INCLUSION - Yuyun Ristianawati; Setyo Budi Hartono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The emergence of financial inclusion in Islamic financial institutions has rendered the financial services offered suboptimal. Decisions available to Islamic financial institutions can determine the form of financial inclusion, the strengths of financial intermediation, and the realization of financial intermediation in investment diversification pathways in the challenges faced by financial intermediation. The study was conducted in Islamic financial institutions, using indicators of the financial inclusion dimension to find non-financial financing methods. The results show that the challenges of FI, the benefits of FI, and the perception of FI have a positive and significant impact on Agility's strategic diversification investment. This suggests that addressing financial inclusion requires an approach that goes beyond financial measures.